2013
DOI: 10.1016/j.jhsa.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Using the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) Statement to Assess Reporting of Observational Trials in Hand Surgery

Abstract: Purpose To use the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement checklist to critically evaluate the change in quality of observational trial reporting in the Journal of Hand Surgery American between 2005 and 2011. Methods A cross-sectional analysis of observational studies published in Journal of Hand Surgery American was designed to sample 2 6-month periods of publication (March 2005 - August 2005 and June 2011 - November 2011). Fifty-one items were extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 69 publications
5
32
1
8
Order By: Relevance
“…In other research fields, like ophthalmology and hand surgery, items like bias (item 9), the explanation of missing data (item 12c), use of a flow-diagram (item 13c) and indicating missing data for each variable of interest (item 14b) scored similarly insufficient to the articles published in ENT journals [21,22]. Items which scored better in these research fields were presenting key elements of study design early in the paper (item 4), defining all outcomes, exposures, predictors, potential confounders and effect modifiers (item 7), describing loss to follow-up/matching of cases and controls/sampling (item 12d) and displaying characteristics of study participants (item 14c).…”
Section: Discussionmentioning
confidence: 99%
“…In other research fields, like ophthalmology and hand surgery, items like bias (item 9), the explanation of missing data (item 12c), use of a flow-diagram (item 13c) and indicating missing data for each variable of interest (item 14b) scored similarly insufficient to the articles published in ENT journals [21,22]. Items which scored better in these research fields were presenting key elements of study design early in the paper (item 4), defining all outcomes, exposures, predictors, potential confounders and effect modifiers (item 7), describing loss to follow-up/matching of cases and controls/sampling (item 12d) and displaying characteristics of study participants (item 14c).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral interventionists need to establish intervention design and implementation reporting conventions (as others have done for other types of interventions and studies [93][94][95] to provide clarity and permit comparability of studies in reviews and meta-analyses. Recent and current efforts to consistently classify behavioral intervention procedures [96][97][98] provide an important component for consistent reporting, but these efforts need to be extended to considerations of theory and non-theory based aspects in interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The concerns over underreporting bias have led to standardized guidelines for conducting observational research (16, 37). Recently, Soresnen et al identified an improvement in the quality of observational research reporting in hand surgery but not in the discussion of potential bias (38). Therefore, it is critical that authors discuss their control population.…”
Section: Discussionmentioning
confidence: 99%